Thermal anomaly in the Nacimiento Block, Monterey County, Central California: differential uplift or hydrothermal event? - Ward, Christine Marie (Kansas State University, 2020)
Within the Coastal Range of California one of the most significant stages in the geodynamics is the passage from subduction to transform motion between the Pacific and North American plates. The subduction of shallow asthenosphere is thought to trigger unusual heat flow, anomalous volcanism, and hydrothermal activities. Past post-subduction thermal overprints have been described in the Franciscan group from the Northern and Central California Coastal Ranges. To date, it is not clear whether the post-subduction thermal anomaly is a response to hydrothermal processes or to rapid vertical uplift by transpressive deformation. In this study we investigate the timing and kinematic processes controlling the thermal anomaly emplacement within the Nacimiento block between the San Gregorio Hozgri Fault (SGHF) and the Nacimiento fault in the Cape San Martin area. In order to address this question we applied (U-Th)/He thermochronological analysis on apatite and zircon grains from metasediments of the Nacimiento block to test whether the thermal anomaly observed resulted from a hydrothermal process or is a response to transpressive deformation. Coupled with Raman Spectroscopy on Carbonaceous Material (RSCM) thermometry on collected samples, we refined the peak temperature map proposed and performed a regional structural analysis to better understand how the thermochronological analysis results fit into the larger set of tectonic processes operating in the area. The results generated show that within the thermal anomaly the regional structures are oriented E-W, which significantly contrasts with the regional fabrics generally oriented N315°- N350°. This drastic orientation change suggests a counterclockwise rotation of about 50°- 75° compared to the regional fabrics. Our low-temperature (U-Th)/He thermochronological analyses show a distinct younging trend from the center of the thermal anomaly, from of 3.87 ± 0.28 Ma (apatite) and 11.77 ± 2.00 (zircon) Ma from the center of the thermal anomaly to 8.10 ± 1.60 (apatite) and 85.13 ± 13.09 Ma (zircon) at the outside edge of the thermal anomaly. Based on these observations and inverse thermal modeling, we infer that the Nacimiento block has undergone subduction of a spreading center (triple junction). There is clear evidence within the Nacimiento block supporting the hypothesis of the subduction of a triple junction including: 1) plutons, 2) high-temperature, low-pressure metamorphic conditions, 3) dikes, and 4) quartz- calcite-sulfide mineralized veins located in the vicinity of the Los Burros Mining District (LBMD). Based on all of the above, we infer that the Nacimiento block is being affected by a combination of hydrothermal activities and transpressive deformation both as a result of subduction of a spreading center.
Keywords: (U-Th)/He thermochronology; RSCM; Nacimiento block; Thermal anomaly; Structural